Settlements and necropoleis of the Black Sea and its hinterland in antiquity : select papers from the third international conference 'The Black Sea in Antiquity and Tekkeköy: an ancient settlement on the southern Black Sea Coast', 27-29 October 2017, Tekkeköy, Samsun - Tsetskhladze, Gocha R.; Tsetskhladze, Gocha R.; Atasoy, Sümer; Atasoy, Sümer (Archaeopress archaeology, 2019)
Papers in this volume cover all shores of the Black Sea and address, alongside many other topics, the establishment dates of some Greek Colonies; East Greek transport amphorae; the history of Tekkeköy; the pre-Roman economy of Myrmekion; Byzantine finds at Komana; glass bracelets from Samsun Museum; dating the Kavak Bekdemir Mosque in Samsun